Transverse versus longitudinal skin incision in first extensor tendon release for radial styloid tenosynovitis: a randomized controlled trial - Sitthiphong Suwannaphisit; Nipat Panichnantho; Warangkana Fongsri; Pormes Suwanno (BMC Musculoskeletal Disorders, 2024)
Abstract Background De Quervain’s tenosynovitis, characterized by the entrapment of the extensor pollicis brevis and abductor pollicis longus tendons in the first extensor compartment, leads to pain and swelling near the radial styloid. When conservative treatments including rest and antiinflammatory medications fail, surgery is often recommended. This study aimed to compare transverse and longitudinal skin incisions with respect to surgical scars, postoperative pain, and functional outcomes in the open release of the first extensor compartment in radial styloid tenosynovitis. Methods Seventy patients were randomly assigned to either the transverse or longitudinal skin incision group using a computer-generated random number table. Postoperative scarring was assessed using the Patient and Observer Scar Assessment Scale (POSAS), pain intensity using a verbal numerical rating scale, and functional outcomes using the Thai version of the Patient-Rated Wrist Evaluation (PRWE) questionnaire at 2, 6, and 12 weeks post-surgery. Continuous data were presented as mean ± standard deviation for normally distributed data or as median (interquartile range) for skewed distributions. Results Following surgery, both groups showed marked improvements in Thai PRWE and POSAS scores, with no differences in functional outcomes. The longitudinal incision group had significant pain reduction at 2 and 6 weeks post-surgery. By 12 weeks, pain alleviation was similar in both groups. Wound infection was not observed in any case, and three patients reported temporary paresthesia, which was not statistically significant between the groups. Conclusions Both techniques demonstrate similar improvements in functional scores and reductions in pain scores, with no significant differences in complication rates, particularly concerning hypertrophic scars. The decision between transverse and longitudinal skin incisions should consider the surgeon’s expertise, the patient’s anatomical characteristics, and the complexity of the surgical procedure. Each approach presents distinct trade-offs, highlighting the necessity of a personalized, patient-centered strategy to optimize surgical outcomes. Trial registration The study was registered on 27/06/2023, at clinicaltrials.in.th (TCTR20230627001). This study was retrospectively registered.